Combinatorial Development and In Vitro Characterization of the Quaternary Zr–Ti–X–Y (X–Y = Cu–Ag/Co–Ni) Metallic Glass for Prospective Bioimplants. Issue 12 (18th October 2019) - Jabed, Akib; Rahman, Zia Ur; Khan, Muhammad Mudasser; Haider, Waseem; Shabib, Ishraq
Abstract : The prospect of Zr‐based metallic glasses (MGs) in achieving a combination of properties, such as excellent electrochemical properties and extended biocompatibility, has been studied in this work. The combinatorial method (magnetron co‐sputtering) has been adopted to fabricate two novel quaternary MG systems (Zr50 Ti32 Cu13 Ag5 and Zr40 Ti37 Co12 Ni11 ) with optimized compositions. The structural analysis has been performed by the grazing incidence x‐ray diffraction and high‐resolution transmission electron microscopy to affirm the disordered structure of the MG systems. The electrochemical analysis demonstrates lower corrosion‐ (0.10 and 0.04 μA cm −2 ), and passive (2.93 and 1.88 μA cm −2 ) current densities of the MGs. In addition, the MGs are found to have higher charge transfer resistance (4.70 and 7.86 MΩ cm 2 ) compared to the 316L stainless steel (SS) (0.15 MΩ cm 2 ) and cp‐Ti (0.53 MΩ cm 2 ). The electrochemical features are indicative towards higher corrosion‐resistance capabilities of Zr50 Ti32 Cu13 Ag5 and Zr40 Ti37 Co12 Ni11 MGs to prevent adverse biological reactions. Additionally, the cell proliferation analysis manifests higher cell proliferation on the Zr50 Ti32 Cu13 Ag5 and Zr40 Ti37 Co12 Ni11 MGs for the MC3T3‐E1 preosteoblast cells. Besides, the MTS assay analysis strengthens the prediction of cytocompatibility of the MGs. The integration of such unique properties makes these MG systems ideal candidates for biomedical implants. Abstract : The fabrication of novel quaternary Zr‐based metallic glass (MG) systems via magnetron cosputtering is assessed, where an in‐depth microstructural characterization and electrochemical analyses of the MGs in body fluid environment are studied. In vitro biocompatibility analyses are conducted to assess the prospect of these proposed MG systems for bioimplant applications as compared with conventional biomaterials.